Hot corrosion behaviour of Ti–6Al–4V modified by ultrasonic shot peening - Kumar S.; Chattopadhyay K.; Mahobia G.S.; Singh V. (My University, 2025)
Nanostructure of 17 to 25 nm was developed in surface region of the titanium alloy Ti–6Al–4V, up to the depth of ~ 30 μm, by ultrasonic shot peening. The effect of nanostructured surface was studied on corrosion behaviour of this alloy, in three different salt mixtures: 100 wt.% NaCl, 75 wt.% Na2SO4 + 25 wt.% NaCl, and 90 wt.% Na2SO4 + 5 wt.% NaCl + 5 wt.% V2O5; at 400, 500 and 600 °C. Specimens were subjected to heating and cooling cycles with different hold periods in three blocks for total exposure of 100 h. The main corrosion products formed in the different salt mixtures were characterized as TiO2, Al2O3, V2O3, Ti2O3 and V2O5 oxides. The corrosion rate was found to be lower in the ultrasonic shot peened specimens as compared to those in the non-shot peened ones. © 2016 Elsevier Ltd